2021
DOI: 10.3390/diagnostics11091691
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Lung Ultrasound (ILU) for the Assessment of Pulmonary Nodules

Abstract: Background: The primary aim of this study was to confirm the validity of intraoperative lung ultrasound (ILU) as a safe and effective method of localization for difficult to visualize pulmonary nodules during Video-Assisted Thoracoscopic Surgery (VATS) and open thoracotomy. The secondary aim was to enhance knowledge on the morphological patterns of presentation of pulmonary nodules on direct ultrasound examination. Materials and methods: 131 patients with lung nodule and indication for surgery were enrolled. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Our first results and practical experience confirm that pulmonary tumours of different sizes (0.6 cm-4.6 cm) and a maximum distance of 6.4 cm to the lung surface can be reliably found intraoperatively by B-mode. This has also been demonstrated in other studies compared to results obtained via manual palpation [3]. Previous studies primarily investigated the value of intrathoracic ultrasound in terms of its ability to detect pulmonary nodules and compared the results with intraoperative palpation [3,5,17].…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Our first results and practical experience confirm that pulmonary tumours of different sizes (0.6 cm-4.6 cm) and a maximum distance of 6.4 cm to the lung surface can be reliably found intraoperatively by B-mode. This has also been demonstrated in other studies compared to results obtained via manual palpation [3]. Previous studies primarily investigated the value of intrathoracic ultrasound in terms of its ability to detect pulmonary nodules and compared the results with intraoperative palpation [3,5,17].…”
Section: Discussionmentioning
confidence: 59%
“…This has also been demonstrated in other studies compared to results obtained via manual palpation [3]. Previous studies primarily investigated the value of intrathoracic ultrasound in terms of its ability to detect pulmonary nodules and compared the results with intraoperative palpation [3,5,17]. In particular, Khereba et al demonstrated the high utility of intraoperative ultrasound for pulmonary nodule detection in minimally invasive thoracic surgery [6].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Preoperative electromagnetic navigational bronchoscopy (ENB) is safe and precise for injecting indocyanine green or iodized oil [19][20][21][22] but is complex, costly, and di cult to generalize. Intraoperative ultrasound is a noninvasive and straightforward approach [23,24] but may fail if the lung tissue is poorly collapsed or contains gas. Three-dimensional reconstruction is noninvasive but requires additional time and technical expertise to create a lung model [25].…”
mentioning
confidence: 99%
“…Almost 2 decades ago, Santambrogio et al [ 10 ] utilized IUS to safely and effectively locate and resect non-palpable PNs in 18 patients. Recently, Taurchini et al [ 11 ] utilized IUS to identify and locate suspicious lung nodules in 131 patients undergoing either thoracoscopic or open thoracotomy resection. The detection rate of lung nodules for ultrasound was 100% compared to digital palpation which was 94.66% [ 11 ].…”
mentioning
confidence: 99%